Newer magnetic resonance imaging techniques in neurocysticercosis. Issue 6 (December 2020) - Batta, Akash; Mahesh, Karthik Vinay; Prabhat, Nandita; Shree, Ritu; Goyal, Manoj K; Ahuja, Chirag K; Rebello, Alex; Tandyala, Naresh; Goyal, Abeer; Choudhary, Aditya; Goyal, Gunjan; Modi, Manish; et al.
Introduction: The definitive diagnosis of neurocysticercosis continues to be challenging. We evaluate the role of newer magnetic resonance imaging techniques including constructive interference in steady state, susceptibility-weighted imaging, arterial spin labelling and magnetic resonance spectroscopy in the diagnosis of neurocysticercosis. Aims and objectives: To study the utility of newer magnetic resonance imaging sequences in the diagnosis of neurocysticercosis. Patients and methods: Eighty-five consecutive patients with neurocysticercosis attending a tertiary care hospital and teaching centre in northern India were included in the study. The diagnosis of neurocysticercosis was made by the Del Brutto criteria. All patients received treatment according to standard guidelines and were followed at 3-month intervals. The following magnetic resonance sequences were performed at baseline: T1 and T2-weighted axial sequences; T2 fluid-attenuated inversion recovery axial sequences; diffusion-weighted imaging; susceptibility-weighted imaging; pre and post-contrast T1-weighted imaging; heavily T2-weighted thin sections (constructive interference in steady state); arterial spin labelling ( n = 19); and magnetic resonance spectroscopy ( n = 24). Results: The mean (±SD) age was 29.4 ± 12.9 years and 76.5% were men. Seizures were the commonest symptom (89.4%) followed by headache (24.3%), encephalitis (9.4%) and raised intracranial pressure (9.4%). Scolex could be visualised in 43.7%, 55.5% and 61.2% of neurocysticercosis patients using conventional, susceptibility-weighted angiography and constructive interference in steady state imaging sequences, respectively. Susceptibility-weighted angiography and constructive interference in steady state images resulted in significantly higher ( P < 0.01) visualisation of scolex compared to conventional sequences. Conclusion: Newer magnetic resonance imaging modalities have a lot of promise for improving the radiological diagnosis of neurocysticercosis.